Effect of Degree of Doneness, Quality Grade, and Time on Instrumental Color Readings from Beef Strip Loin Steaks Cooked to Six Degrees of Doneness - L. L. Prill; L. N. Drey; J. L. Vipham; M. D. Chao; J. M. Gonzalez; T. A. Houser; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2019)
Objective:The objective of this study was to determine the effect of quality grade and time after cooking on the instrumental color of steaks cooked to varying degrees of doneness. Study Description:Beef strip loins (n = 24) from 12 animals representing five quality treatments [Prime, Top Choice, Low Choice, Select, Select Enhanced (108%)] were collected. Each steak was cooked to a peak internal temperature of very-rare (130°F), rare (140°F), medium-rare (145°F), medium (160°F), well-done (170°F), or very well-done (180°F). Each cooked steak was cut in half, perpendicular to the long axis of the steak, and lightness (L*), redness (a*), and yellowness (b*) was evaluated on the internal face of the medial side at 0, 1, 2, 3, 6, 9, and 12 minutes post-cutting using a Hunter Lab Miniscan spectrophotometer. The Bottom Line:The impact of time on internal cooked color was dependent on degree of doneness, with steaks cooked to lower degrees of doneness becoming lighter and more red in color with time and steaks cooked to higher degrees of doneness becoming darker. Additionally, quality treatment had no impact on cooked color measures of non-enhanced steaks. These results provide insight into cooked beef color changes related to time and how this might impact degree of doneness perceptions by consumers.
Keywords: degree of doneness; quality grade; time